Impacts of extreme events on hydrodynamic characteristics of a submerged floating tunnel - Zou, P.X.; Bricker, Jeremy D.; Uijttewaal, Wim S.J. (Ocean engineering, 2020)
A submerged floating tunnel (SFT) is a promising alternative to conventional bridges and tunnels, and can be potentially built in the Qiongzhou Strait in China. However, this area is under the threat of disasters including mega tsunamis and severe storm surges. To evaluate the hydrodynamic loads of the SFT in this hazardous zone subject to severe tsunami and typhoon impacts, the Delft3D-FLOW hydrodynamic model and SWAN wave model are coupled, and a Computational Fluid Dynamics (CFD) method is adopted. The maximum probable tsunami and typhoon Rammasun (July 2014) are selected as hazard assessment conditions in the Qiongzhou Strait. Whether the tsunami and hindcast storm surge cause extreme forcing and bring challenges to the SFT engineering design, operation, and maintenance in the Qiongzhou Strait are discussed in this study. We reveal that the typhoon impacts are more devastating than tsunami for an SFT in the Qiongzhou Strait. In order to determine the optimal SFT cross-section under extreme events, we use a parametric Bezier curve profile compared with two simpler shapes including circular and elliptical cross sections. In-line force and lift are respectively applied to evaluate the SFT's hydrodynamic behaviour. Our results reveal that the gross horizontal force on the parametric Bezier curve shape is more sensitive to flow acceleration, while the circular cross-section is dominated by current speed. The parametric Bezier curve cross-section shape has the preferable property of reducing the in-line force and postponing serious vortex shedding compared with the two simpler shapes. •Extreme disasters including mega tsunamis and severe storm surges accessed in the Qiongzhou Strait.•An integrated atmosphere-ocean modelling combined with CFD framework established for tunnel forcing evaluation.•Preferable property of a parametric submerged floating tunnel cross-section than the simpler shapes.•The typhoon impacts are more devastating than tsunami for the submerged floating tunnel in the Qiongzhou Strait.